2021
DOI: 10.17582/journal.aavs/2022/10.1.160.169
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Phytochemical, Antioxidant and Antibacterial Activity of Balanites Aegyptiaca and Curcuma Longa against Some Bacterial Pathogens Isolated from Dairy Cow Infected with Mastitis

Abstract: Bovine mastitis is very important disease threatening the dairy industry and animal wealth globally, resulting in great economic losses. The present work was aimed to assess the phytochemical components, antioxidant activity and the antibacterial effectiveness of Balanites aegyptiaca fruits (BAF) and Curcuma longa powder (CLP) extracts. A total of 287 quarter milk samples were collected from dairy cows raised in four different governorates of Egypt; 95 from clinical mastitis, 37 from subclinical mastitis and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Recent studies have confirmed the medicinal use of different extracts of B. aegyptiaca fruits in the treatment of hyperactive gut disorders [ 19 ], diabetes mellitus [ 20 ], hyperglycemia [ 21 ], and dermatophytes [ 22 ]. The antibacterial activity of B. aegyptiaca fruit extract has been reported by several previous studies against a number of fungal and bacterial species [ 3 , 22 , 23 , 24 , 25 , 26 , 27 ]. These effects are ascribed to phytochemicals detected in the extract including palmitic acid [ 28 , 29 ] and hexadecanoic acid, 2,3-dihydroxypropyl ester.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Recent studies have confirmed the medicinal use of different extracts of B. aegyptiaca fruits in the treatment of hyperactive gut disorders [ 19 ], diabetes mellitus [ 20 ], hyperglycemia [ 21 ], and dermatophytes [ 22 ]. The antibacterial activity of B. aegyptiaca fruit extract has been reported by several previous studies against a number of fungal and bacterial species [ 3 , 22 , 23 , 24 , 25 , 26 , 27 ]. These effects are ascribed to phytochemicals detected in the extract including palmitic acid [ 28 , 29 ] and hexadecanoic acid, 2,3-dihydroxypropyl ester.…”
Section: Introductionmentioning
confidence: 82%
“…These results indicate that B. aegyptiaca fruit extract is a potent antimicrobial agent according to the categories reported by Kuete [ 50 ] classifying substances with MICs below 0.1 mg/mL as potent antimicrobial agents. The antibacterial activity of B. aegyptiaca fruit extract has been reported by several previous studies against a number of fungal and bacterial species such as Candida albicans and Staphyloccous aureus [ 3 , 25 ], Aspergillus [ 3 , 23 , 24 ], Fusarium [ 26 , 27 ] and dermatophytes [ 22 ]. This effect is related to the bioactive phytochemicals detected in the extract mainly oleic and palmitic acids which were the prevalent components recording 24.12 and 21.56%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly significant for immunocompromised patients who may encounter challenges with antifungal drug resistance, highlighting the therapeutic promise of these natural extracts. [27]…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Fresh basil leaves were obtained from National Research Centre in Giza, Egypt, and dried in the sun light for a week and mashed into powder. It was extracted according to the techniques described by (Sedky et al, 2022) the basil powder as much as 100g was macerated using 500 ml ethanol 80% over three days for 24h in room temperature and then filtered by cheesecloth and repeated the filtration 3 times and then evaporated the solution using a rotary evaporator vacuum. The obtained crude extract which weighted 2.831g was dissolved in 100 ml ethanol 80% then prepared the mentioned concentrations (v/v).…”
Section: Preparation Of Basil Leaves Extractmentioning
confidence: 99%